1
$\begingroup$

I am familiar with two different sets of field axioms. The first one is from "Mathematical Analysis" by Apostol. It has the first $3$ usual axioms, but the $4^{th}$ one is different:

Axiom 1: Commutative Laws

$x+y=y+x$, $xy=yx$

Axiom 2: Associative Laws

$x+(y+z)=(x+y)+z$, $x(yz)=(xy)z$

Axiom 3: Distributive Law

$x(y+z)=xy+xz$

Axiom 4:

Given any two real numbers $x$ and $y$, there exists a real number $z$ such that $x+z=y$. This $z$ is denoted by $y-x$; the number $x-x$ is denoted by $0$ (it can be proved that $0$ is independent of $x$.) We write $-x$ for $0-x$ and call $-x$ the negative of $x$.


Subtraction doesn't immediately follow as an operation from axiom 4, but we can prove that $y-x=y+(-x)$ and define subtraction this way. However, more commonly have seen axiom 4 being replaced by

$x+ (-x) = 0$

$x + 0 = x$

How do we introduce subtraction with this set of axioms? I have seen problems giving the second version of axiom 4 and having $y-x$, should I just assume it's meant as $y+(-x)$?

$\endgroup$
  • 1
    $\begingroup$ In your second set of axioms, how do you define $-x$? Usually, we are given that the underlying set, together with addition, is an abelian group, so that $-x$ is by definition the additive inverse of $x$, and then we may define $y - x = y + (-x)$. $\endgroup$ – Alex Provost Dec 26 '15 at 19:00
  • $\begingroup$ Hm well that's all I had, I just started analysis so I'm not familiar with abelian groups, or any sort of groups $\endgroup$ – Ovi Dec 26 '15 at 19:08
  • $\begingroup$ I think your second set of axioms is postulating the existence of an additive inverse of $x$, denoted $-x$. This is really the same thing as what's being done in your first set of axioms. $\endgroup$ – Alex Provost Dec 26 '15 at 19:14
  • $\begingroup$ @A.P. But I think from axiom 4 we can define the subtraction operator by proving $y-x=y+(-x)$. Then, I wanted to start from the second set of axioms and prove that $y+(-x)=y-x$, but I found I couldn't do that because those axioms hadn't really defined $y-x$. So do we just define $y+(-x)=y-x$ if starting with the second set? $\endgroup$ – Ovi Dec 26 '15 at 19:19
  • $\begingroup$ I wrote an answer addressing your concerns in more detail. $\endgroup$ – Alex Provost Dec 27 '15 at 3:38
3
$\begingroup$

Edit: In order to prove unicity of the element $0$ defined in Axiom 4, it seems necessary to upgrade Axiom 4 to a stronger statement, namely:

Axiom 4:

Given any two real numbers $x$ and $y$, there exists a unique real number $z$ such that $x+z=y$. This $z$ is denoted by $y-x$; the number $x-x$ is denoted by $0$ (it can be proved that $0$ is independent of $x$.) We write $-x$ for $0-x$ and call $-x$ the negative of $x$.


Hopefully this clears up the remaining confusion.

Axiom 5: There exists a real number $0$ such that $z + 0= z$ for any real number $z$. For any real number $x$, there exists a real number $-x$ satisfying $x + (-x) = 0$.

Note that $0$ is unique, for if $0'$ is another such number then $0 = 0 + 0' = 0'$. Also note that the inverse element $-x$ is uniquely determined by $x$, for if $z$ is any other number such that $x + z = 0$, we must have $$z = z + 0 = z + (x + (-x)) = (z + x) + -x = 0 + (-x) = -x.$$ (Note that we need associativity here.)

Fact: Axiom 4 $\iff$ Axiom 5.

Assume Axiom 4 holds. Define $0 := z -z$, where $z$ is any real number. Axiom 4 assures us that this is a well-defined real number and that $z + 0 = z$ for any real number $z$. Given a real number $x$, we set $-x := 0 - x$, which is a real number whose existence is assured by Axiom 4. By the definition of $0 - x$ given in Axiom 4, this means that $x + (-x) = 0$, so Axiom 5 is satisfied.

Conversely, assume Axiom 5 holds. Let $x,y$ be real numbers. To prove Axiom 4, we need to define a real number $y - x$ satisfying $x + (y-x) = y$, and prove that it is unique. In fact, if this relation were to hold, we could add the number $-x$ provided by Axiom 5 to both sides to get (using commutativity and associativity) $$ y + (-x) = x + (y-x) + (-x) = x + (-x) + (y-x) = 0 + (y-x) = y - x.$$ Hence we see that we have to define $y - x := y + (-x)$, where $-x$ is the real number whose existence is assured by Axiom 5. This gives us the unicity part. Then, by the definitions of $-x$ and $0$ given in Axiom 5 and the other axioms we have that $x+ (y-x) = x + y + (-x) = x + (-x) + y = 0 + y = y$, which proves the existence part and hence Axiom 4.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Hm well you proved existence at the end, but it seems to me like you already assumed existence by defining $y-x$ such that $x+(y-x)=y$ $\endgroup$ – Ovi Dec 28 '15 at 22:41
  • $\begingroup$ @Ovi I didn't assume existence. I showed that there exists a number $y-x$ such that $x + (y-x) = y$ by defining $y-x:= y +(-x)$. I never assumed that this $y-x$ existed in the first place to prove this. (Unless you are referring to the unicity part?) $\endgroup$ – Alex Provost Dec 28 '15 at 22:54
  • $\begingroup$ But you said "we define a real number $y-x$ satisfying $x + (y-x)=y$. But don't you have to prove first that $x+z=y$ is satisfiable to begin with? $\endgroup$ – Ovi Dec 29 '15 at 3:13
  • $\begingroup$ @Ovi I said "we need to define a real number $y-x$..."; at this point I am not claiming that $y-x$ is defined; I am defining it later when I say that $y-x := y + (-x)$. What do you mean by "$x+z=y$ is satisfiable"? $\endgroup$ – Alex Provost Dec 29 '15 at 5:54
  • $\begingroup$ Oh ok now I see your logic in that regard. What I mean by $x+z=y$ being satisfiable is that in axiom 4, we are told explicitly that for any $x$, $y$, there exists a $z$ such that $x+z=y$. Because this statement is by itself in it's own sentence, leads me to believe that the existence of $z$ does not follow directly from the definition of addition, but it must be given as part of the axiom. What I'm concerned about is that I don't see how the existence of $z$ is guaranteed by axiom $5$. $\endgroup$ – Ovi Dec 29 '15 at 6:29
3
$\begingroup$

Subtraction $y-x$ is defined as $y+(-x)$, where $-x$ is defined in axiom 4.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.